The Effect of Product Quality, Service Quality, and Physical Environment on Repurchase Intention through Customer Satisfaction in Jatinangor House Sorowajan - Nawawi, Mohammad Hisyam; Wisnalmawati, Wisnalmawati; Sutiono, Heru Tri (CV. Strata Persada Academia, 2025)
This research aims to examine the influence of product quality, service quality, physical environment influence customer satisfaction. Customer satisfaction influence repurchase intention. Product quality, service quality, physical environment influence intentions which are mediated by customer satisfaction. Methods: This research examines the effect of product quality, service quality, physical environment on repurchase intentions. Sample taken from consumers in Jatinangor house sorowajan. The number of samples in this research was 80 respondents. The sampling technique uses accidental, namely distributing questionnaires to consumers who meet in WhatsApp groups. The data was tested with the variable product quality, service quality, physical environment, repurchase intention. Data were analyzed using the Structural Equational Model (SEM) with Partial Lease Square (Smart PLS) technique. Results: The research results show that the product quality, physical environment influence customer satisfaction. Except for service quality does not have a significant effect. Customer satisfaction influence repurchase intention. Product quality, service quality, physical environment influence intentions which are mediated by customer satisfaction. Novelty: The novelty of this research is that customer satisfaction can increase the repurchase intention on Jatinangor house Sorowajan. Theory implications – The findings of this study may contribute to consumer behavior models, Practical implications Strategizing product, service, and physical environment Jatinangor house Sorowajan, and Triple duties.